2007
DOI: 10.1007/s00421-007-0620-7
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the haemostatic system after thermoneutral and hyperthermic water immersion

Abstract: Warm water bathing is a popular recreational activity and is frequently used in rehabilitation medicine. Although well tolerated in most cases, there are reports indicating an increased risk of thrombotic events after hot tub bathing. The effects of a 45 min thermoneutral bath followed by a 50 min bath with increasing water temperature (maximum 41 degrees C) until reaching a body core temperature of 39 degrees C on factors of blood coagulation and fibrinolysis were studied in eight healthy male volunteers. Blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Specifically, the PT is shortened if there is an increase in factor II, V, VII, X and/or fibrinogen [29]. The shortened PT may also be related to the increased body temperature [4]. …”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the PT is shortened if there is an increase in factor II, V, VII, X and/or fibrinogen [29]. The shortened PT may also be related to the increased body temperature [4]. …”
Section: Discussionmentioning
confidence: 99%
“…Forty-five minutes of TN HOWI followed by warm water immersion at 41 • C caused an immediate decrease of plasma fibrinogen and plasminogen activator inhibitor activity concentration decreased immediately. These observation suggest that warm HOWI leads to hemoconcentration and minimal activation of coagulation, implying increased risk of thrombotic activity (32).…”
Section: Head-out Water Immersion In Warm Watermentioning
confidence: 98%
“…During the time after injury, the patient did not practice any exercises. In the literature, there are some observations of physically active patients with deep venous thrombosis [5,18]. A repeatedmeasures cohort study, conducted on 41 subjects indicated that exercise did not acutely exacerbate post-thrombotic symptoms and, in subjects with PTS, effected in improved flexibility in the affected leg [5].…”
Section: Resultsmentioning
confidence: 99%
“…Scientists conclude that training may help prevent or improve the post-thrombotic syndrome, as early walking exercise was safe in patients with acute DVT and helped lower acute symptoms [4]. Regular sport practice also reduced the risk of DVT recurrence in patients [18].…”
Section: Resultsmentioning
confidence: 99%